SMALL CLAIMS DISPUTES IN THE LIGHT OF THE NOVELCPA 2022. - Marko Spahija (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The provisions of Articles 80-87 of the Law on Amendments to the Civil Procedure Law ("Official Gazette" No. 80/2022, hereinafter: ZIDZPP/22) amended the provisions regulating civil proceedings in small claims disputes. The aforementioned law entered into force on July 19, 2022, and the provisions related to small claims disputes apply to all proceedings initiated after the stated date, with certain exceptions (Articles 83, 84 and 85 ZIDZPP/22). In this paper, the novelties foreseen by the mentioned law will be elaborated, which will affect the proceedings of small claims disputes.